Application of Minocycline-Containing Bismuth Quadruple Therapies as First-Line Regimens in the Treatment of Helicobacter pylori - Lingyun Zhang; Yu Lan; Qi Wang; Yuexia Zhang; Xiaobei Si (Gastroenterology Research and Practice)
Aim. To evaluate the eradication rate, safety, and compliance of minocycline-containing bismuth quadruple regimens in patients with an untreated Helicobacter pylori (H. pylori) infection. Methods. A total of 360 patients with an untreated H. pylori infection were enrolled in this study between June 2017 and October 2018. Patients were randomly divided into a minocycline/amoxicillin (RMAB) group, a minocycline/metronidazole (RMMB) group, or an amoxicillin/clarithromycin (RACB) group, and all groups received a combined treatment approach with rabeprazole and bismuth to create a quadruple regimen for 14 days. A 3 to 5-day follow-up was adopted to evaluate the safety and compliance of medications after medicine administration. 13C-urea breath test was performed to confirm the eradication of H. pylori 4-12 weeks after therapy. Results. No significant differences were observed at baseline data among the three groups (p>0.05). Based on the intent-to-treat analysis, the eradication rates of the RMAB group, RMMB group, and RACB control group were 85.7% (102/119), 77.1% (91/118), and 71.7% (86/120), respectively, with significant difference (χ2=7.015, p=0.030). According to per protocol analysis, the eradication rates of RMAB group, RMMB group, and RACB group were 89.5% (102/114), 84.3% (91/108), and 76.8% (86/112), respectively, with statistically significant differences (χ2=6.673, p=0.036). The eradication rates of the RMAB group and RACB group were significantly different (p<0.05). The overall incidences of adverse events in the three groups were 30.0%, 37.5%, and 40.0%, respectively (p>0.05). Nausea, epigastric discomfort, and dizziness were more obvious in patients in the RMMB group compared to the other two groups (p<0.05). Moreover, two patients discontinued due to severe dizziness and nausea in the RMMB group. A taste disorder was more prominent in patients in the RACB group compared to patients in the other two groups (p<0.05), and one patient discontinued because of the bitterness in the mouth. Soon after discontinuation of the medicine, all adverse events disappeared. Conclusion. The bismuth quadruple regimen using minocycline/amoxicillin showed a better eradication effect with fewer side effects in patients with untreated H. pylori infections. The bismuth quadruple regimen with minocycline/metronidazole had a good eradication effect with more obvious side effects and might be recommended to patients with penicillin allergy.